Plotinus : an introduction to the Enneads - O'Meara, Dominic J. (Clarendon Press ; Oxford University Press, 1993)
"This book is addressed to readers new to the Enneads. One of the greatest of ancient philosophers, Plotinus is attracting ever-increasing attention from those interested in ancient philosophy, late Antiquity, and the importance of this period for the Western intellectual tradition. O'Meara presents a brief outline of Plotinus's life, and of the composition of the Enneads, placing Plotinus within the intellectual context of the philosophical schools and religious movements of his time. He then discusses selected Plotinian texts in relation to a number of central philosophical issues to show how Plotinus's thinking on these issues evolved, and to assess the historical importance of his philosophy." http://www.loc.gov/catdir/enhancements/fy0638/92024776-d.html